Are referendums directly democratic? - Trueblood, L (Oxford University Press, 2020)
Referendums are regularly defined as being directly democratic. Indeed, the term ‘direct democracy’ is often used synonymously with referendums. The label ‘direct democracy’ is used to make two different types of claims about referendums: (i) descriptive claims about what referendums are; and (ii) normative claims about how their use is justified. This article challenges the treatment of referendums as devices of direct democracy both in theory and in practice. I argue instead that referendums should be theoretically and practically understood as processes that provide direction to representatives. Indeed, one consequence of my argument is the broader claim that the term ‘direct democracy’ is generally misleading. In a contemporary context, all democratic processes are—at least in part—representative.